A Historical Approach to Shifting Technologies of Ceramic Manufacture at Gaspereau Lake, Kings County, Nova Scotia - Woolsey, Cora A. (My University, 2018)
A lengthy history (1550–950 Cal BP) of ceramic manufacture took place at the Gaspereau Lake Reservoir (GLR) Site Complex in Kings County, Nova Scotia, during which potters shifted their practice from fineware, emphasizing self-expression and signalling affiliation, to “production” pottery, focusing on quick turnaround times and larger scale of production. Researchers in the Maine–Maritimes Region have repeatedly noted the change from hard-bodied, thin-walled, elaborately and carefully decorated pots during the Middle Woodland to coarser-tempered, expediently decorated pottery with many coil breaks evident during the Late Woodland. This has sometimes been interpreted as a decreasing skill level through time, but I argue that these changes instead suggest a manufacturing context in which demand for pottery increased. This created incentives for “cutting corners” and employing strategies that increased the survival rate of pots during firing. Increased production is partly evident in increasing standardization of temper minerals and clay later in time, suggesting that potters increasingly accessed a single reliable source of raw materials rather than many different sources. I further argue that manufacturing occurred at or near the End of Dyke Site. I present a method of analyzing ceramics that is designed to take full account of the unusually large and nuanced GFC assemblage. This method goes beyond chronological and typological classifications that have sometimes been employed in the Northeast: it seeks to establish a historical understanding of the assemblage through tracing learning lineages. This classification, which I have called a “tradition-based classification,” introduces knowledge transfer as the dominant mechanism behind style at the level of assemblage. The ceramics have been grouped using attribute analysis, after which inferences about the variability have been assessed, and finally, several trends—chronologically situated using AMS dates—are proposed to build a history of ceramic manufacture at Gaspereau Lake.
Keywords: Maritime Woodland Period; Aboriginal ceramics; Gaspereau Lake; Nova Scotia archaeology; Maine-Maritimes Region